Analysis of interface trap parameters from double-peak conductance spectra taken on N-implanted 3C-SiC MOS capacitors - Krieger, Michael; Beljakowa, Svetlana; Trapaidze, Lia; Frank, Thomas; Weber, Heiko B.; Pensl, Gerhard; Hatta, N.; Abe, M.; Nagasawa, H.; Schöner, Adolf (physica status solidi (b), 2008)
3C-SiC/SiO2 capacitors are fabricated by over-oxidation of an implanted Gaussian nitrogen (N) profile and investigated by conductance spectroscopy. An unexpected double peak structure is observed in the conductance spectra indicating two types of independent traps at different energy positions in the bandgap, which change their charge state with identical time constant. A theoretical model is developed assuming two independent distributions of interface traps in the bandgap of 3C-SiC with different trap parameters. The experimental G/ω-V and C-V spectra are simulated and the trap parameters are determined on the basis of this model. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.
UnivIS-Import:2015-04-14:Pub.2008.nat.dphy.IAP.LAP.analys

Characterization of Ge-doped homoepitaxial layers grown by chemical vapor deposition - Sledziewski, Tomasz; Beljakowa, Svetlana; Alassaad, Kassem; Kwasnicki, Pavel; Arvinte, Roxana; Juillaguet, Sandrine; Zielinski, Marcin; Souliere, Veronique; Ferro, Gabriel; Weber, Heiko B.; Krieger, Michael (Materials Science Forum, 2014)
We have investigated the electrical properties of n-type 4H-SiC in-situ germanium-doped homoepitaxial layers grown by chemical vapor deposition. Germanium is an isoelectronic impurity and, therefore, not expected to contribute to the conductivity. However, Hall effect measurements taken on samples with and without germanium revealed an enhanced mobility by a factor of ≈2 at T ≈ 55 K in the germanium-doped sample despite equal free electron concentration and equal compensation. Deep level transient spectroscopy (DLTS) measurements taken on germanium-doped samples reveal negative peaks indicating the presence of charged extended defects. © (2014) Trans Tech Publications, Switzerland.
UnivIS-Import:2015-04-14:Pub.2014.nat.dphy.IAP.LAP.charac
Keywords: Admittance spectroscopy; DLTS; Ge-doping; Hall effect; Hall mobility

Effect of germanium doping on electrical properties of n-type 4H-SiC homoepitaxial layers grown by chemical vapor deposition - Sledziewski, Tomasz; Vivona, M.; Alassaad, K.; Kwasnicki, P.; Arvinte, R.; Beljakowa, Svetlana; Weber, Heiko B.; Giannazzo, F.; Peyre, H.; Souliere, V.; Chassagne, T.; Zielinski, M.; et al. (Journal of Applied Physics, 2016)
The effect of germanium (Ge) on n-type 4H-SiC is experimentally studied by electrical characterization of homoepitaxial layers grown by chemical vapor deposition (CVD). Measurements show that electrical properties of epitaxial layers can be changed by intentional incorporation of germane (GeH4) gas during the deposition process. On the nanoscale, two-dimensional mappings acquired with conductive atomic force microscopy show preferential conductive paths on the surface of Ge-doped samples, which are related to the presence of this isoelectronic impurity. Hall effect measurements confirm that also macroscopic electrical properties of n-type 4H-SiC are improved due to incorporation of Ge into SiC during CVD growth. In particular, despite equal free electron concentration, enhanced mobility in a wide temperature range is measured in Ge-doped samples as compared to a pure 4H-SiC layer. Based on our results from Hall effect measurements as well as admittance spectroscopy and deep level transient spectroscopy, it is speculated that Ge influences the generation and annealing of other point defects and thus helps to reduce the total concentration of defects. Published by AIP Publishing.

Persistent Conductivity in n-type 3C-SiC Observed at Low Temperatures - Beljakowa, Svetlana; Hauck, Martin; Bockstedte, Michel Georg; Fromm, Felix; Hundhausen, Martin; Nagasawa, H.; Weber, Heiko B.; Pensl, Gerhard; Krieger, Michael (Materials Science Forum, 2014)
Persistent conductivity in n-type 3C-SiC is investigated in a wide temperature range down to 3 K by Hall effect, admittance spectroscopy, low temperature photoluminescence (LTPL) and Raman spectroscopy. We propose a model, which clearly explains the persistent behavior of the electron density η below 50 K. It is experimentally verified that the persistent conductivity results from doped SF bunches, which can be considered nano-polytype inclusions in 3C-SiC. © (2014) Trans Tech Publications, Switzerland.
UnivIS-Import:2015-04-14:Pub.2014.nat.dphy.IAP.LAP.persis
Keywords: 3C-SiC; Hall effect; Persistent conductivity; Raman spectroscopy; Stacking faults (SFs)